The Evaluation of Professional Placement in Public Vocational High School 2 Tegal by Using Stake Countenance Model - Windrajaya, Eko Rudy; Hardyanto, Wahyu; Wibawanto, Hari (Universitas Negeri Semarang, 2020)
This research is conducted because of the background of professional placement which is never be done. Thus the success couldn’t be seen. This research used Stake Countenance Model. The research method is qualitative descriptive by data collection technique of observation, interview, and documentation study. The research purpose is to evaluate the implementation of Professional Placement by using Stake Countenance. Result study shows that (1) Antecedents, covering the vocational competence election is implemented before professional placement or PKL, there are forty Du/Di, the activities had done for six months, the material is arranged by school without involving Du/Di, the briefing is done in two cycles, the determination of advisor is determined by the productive teachers and Du/Di, (2) Transactions, covering the journal is conducted by the students and evaluated by the advisers, monitoring is done in two cycles, the composing of the report is guided by the teacher adviser and the Du/Di, (3) Output, covering the evaluation involves the cognitive aspect, attitude, and skills but there is no test for students, there are only three Du/Di which delivers the certificates, research result shows that from ninety-seven (97) students’ of Office Administration in class eleven, there were only fifty-two (52) students who reached predicate A in range (90-100), and forty (40) students got predicate B in range (80-89), and five (5) students got predicate C in range (70-79). Based on the research result on this professional placement, the eleventh grade Office Administration students of Public Vocational High School 2 Tegal is work. The implication at improvement of professional placement in Public Vocational High School 2 Tegal is the arrangement of materials should be composed by the school with Du/Di, doing the test for students, the adviser’s expertise competence must be appropriate, and Du/Di have to give the task which is appropriate to the students’ expertise competence.